(untitled) (Research, Society and Development, 2023)
Thrombocytopenia is defined by a platelet count of less than 150,000 000/ul and can be classified as mild, moderate, or severe. Counts below 150,000 and above 100,000/ul do not necessarily indicate disease. Platelets are cytoplasmic fragments of megakaryocytes, circulate inactivated, and are found in the form of their precursors in the bone marrow. Removed by macrophages, they have an essential function in hemostasis and maintenance of the capillary endothelium. Screening in primary care is essential because the vast majority of thrombocytopenias are present in asymptomatic patients, with isolated thrombocytopenia identified incidentally. These situations without a specific diagnosis do not require hematologic follow-up. This case study aimed to identify that a large number of patients referred to the Hematology Outpatient Clinic of the Assis Gurgacz Faculty (FAG) do not have a confirmed diagnosis of thrombocytopenia. Data will be collected by evaluating medical records of patients referred to the Hematology Outpatient Clinic of Assis Gurgacz College (FAG) in the period between 2018 and 2021 for the finding of thrombocytopenia at primary diagnosis.